2016
DOI: 10.1038/nrclinonc.2016.64
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of metronomic chemotherapy: a neglected but crucial aspect

Abstract: Metronomic chemotherapy describes the close, regular administration of chemotherapy drugs at less-toxic doses over prolonged periods of time. In 2015, the results of randomized phase III clinical trials demonstrated encouraging, albeit limited, efficacy benefits of metronomic chemotherapy regimens administered as adjuvant maintenance therapy for the treatment of breast cancer, or as maintenance therapy in combination with an antiangiogenic agent for metastatic colorectal cancer. Owing to the investigational na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
132
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(136 citation statements)
references
References 142 publications
1
132
0
3
Order By: Relevance
“…Based on our IMC finding that cisplatin is extensively bound to collagen, we suggest this could have a significant effect within the tumor microenvironment due to the slow release of drug in sufficient amounts to affect tumor growth. It is reported that continuous exposure to low dose metronomic chemotherapy improves the therapeutic index of some cytotoxic agents31, although we are unaware that this has been tested with platinum compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our IMC finding that cisplatin is extensively bound to collagen, we suggest this could have a significant effect within the tumor microenvironment due to the slow release of drug in sufficient amounts to affect tumor growth. It is reported that continuous exposure to low dose metronomic chemotherapy improves the therapeutic index of some cytotoxic agents31, although we are unaware that this has been tested with platinum compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Metronomic dosing schedules advocate smaller, more frequent dosing 10, 11 . These new dosing approaches are predicated on both the timing of therapy administration and response evaluation 12 but have revealed a fundamental limitation in the current understanding of the pharmacokinetic (PK) and pharmacodynamic (PD) properties of cytotoxic agents. While the potency, efficacy, and mechanism of action of these agents have been the target of study for years, these pharmacologic properties are inherently insufficient to predict the spatiotemporal response of individual tumors to treatment, limiting the ability to realize these theoretical dosing schedules.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, long-term MC is oriented towards the lowest dose necessary, and small changes in drug metabolism may result in steady state drug levels below the threshold needed for optimal anti-tumor activity [52,53]. While certain chemotherapeutics may induce their own metabolism, steady state drug levels may also be affected by pharmacogenomic traits, concurrent medications, treatment adherence, or organ dysfunctions commonly seen in elderly patients.…”
Section: Mechanisms Of Resistance To Metronomic Chemotherapymentioning
confidence: 99%
“…There are only a few dedicated MC pharmacokinetic studies available, the major findings of which have been reviewed recently [53]. Preclinical studies are reassuring in a number of ways.…”
Section: Mechanisms Of Resistance To Metronomic Chemotherapymentioning
confidence: 99%